2003
DOI: 10.1076/jcen.25.3.324.13802
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Estimation and Affective Judgments in Alcoholic Korsakoff Patients

Abstract: Alcoholic Korsakoff patients have their most marked deficits in memory, but may exhibit problems in further cognitive and behavioral domains, particularly in so-called frontal lobe functions and on the emotional level. Cognitive estimation is among the frontal lobe-associated functions; nevertheless, the underlying processes of estimation and estimation deficits are still unknown. Additionally, though affective judgments were found to be disturbed in Korsakoff patients one can question whether this result is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 55 publications
7
45
1
Order By: Relevance
“…For instance, Snitz, Hellinger and Daum (2002) found deficits in the ability to identify affective prosodies in spoken sentences. In line with these results KS patients in the study of Brand et al (2003a) were impaired in classifying nouns according to their emotional valence as positive, negative, or neutral. The authors reported that patients showed a marked tendency to judge neutral and negative words as positive.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…For instance, Snitz, Hellinger and Daum (2002) found deficits in the ability to identify affective prosodies in spoken sentences. In line with these results KS patients in the study of Brand et al (2003a) were impaired in classifying nouns according to their emotional valence as positive, negative, or neutral. The authors reported that patients showed a marked tendency to judge neutral and negative words as positive.…”
Section: Introductionsupporting
confidence: 83%
“…The first trial of this task, designed to measure affective judgment abilities, contained 15 nouns with different affective valences (5 positive, 5 negative, and 5 neutral words; see Brand et al, 2003a). The order of word presentation was randomized.…”
Section: Experimental Tasksmentioning
confidence: 99%
See 2 more Smart Citations
“…These patients often show attentional and anterograde memory deficits beyond executive dysfunctions (Airaksinen Table 1. Results in the neuropsychological test battery (for test description see Brand et al, 2003;Spreen and Strauss, 1998) Egeland et al, 2003). ZZ showed average to above average performance in all tested neuropsychological domains except for executive functions (Table 1).…”
Section: Discussionmentioning
confidence: 98%